The Future of Nothingness: Plastic Apocalypticism or an Insistent Messianic? - Ullrich, Calvin D. (Stellenbosch Theological Journal, 2022)
Tentatively emerging from a global pandemic, we are confronted with a horizon of immanent adversities: (1) the closing window for altering the trajectory of our climate crisis, (2) the political antagonisms that exacerbate greater polarization, and (3) the effects of late-stage capitalism that service these first two interconnected configurations. Far from indulging a doomsday pessimism or comfortable misanthropy, this article pursues two continental philosophers, situating them within the tradition of "negative political theology" to think through a future of nothingness. Developing and then distinguishing between what is called the "plastic apocalypticism" of the philosopher Catherine Malabou, which thinks the end of the world as such, and an "insistent messianic" of the radical theologian, John D. Caputo, which takes the end of the world as the condition for saving it, an argument is made in favour of a mutual compatibility - recognizing the passing away of this world, its absolute contingency, but also the "event" of God's insistence. This messianic insistence and plastic revelation both resist divine intervention and instead look toward the formation of a new future, just as such a future (of nothingness) is the condition for the persistent interrogative of all concrete political arrangements.